Communicative Competence of Nurses in the Lens of Patients - Davila, Rose Ann Erlie A. (Celebes Nursing Journal, 2025)
Introduction: Communication is central to effective nursing care and patient outcomes. Objective: This study aimed to assess nurses’ communicative competence as perceived by patients, focusing on the following domains, namely; interest in the patient as a person, understanding patient’s experience of illness, attention to context, and participation in care. Methods: Using a descriptive correlational design, the study surveyed 626 admitted patients from both public and private hospitals in Borongan City, adapting the validated 18-item Rochester Communication Rating Scale. Descriptive statistics summarized the patient respondents’ socio-demographic profiles, and Spearman’s rank correlation examined relationships between these variables and perceived communicative competence of nurses. Results: Showed that nurses demonstrated satisfactory communicative competence overall, with the highest ratings in understanding patient’s experience of illness (M=3.72, SD=0.939) and participation in care (M=3.71, SD=0.918), and comparatively lower scores in interest in the patient as a person (M=3.63, SD=0.900), and attention to context (M=3.28, SD=1.343). Correlational analysis revealed no significant relationships between socio-demographic profiles and perceived communicative competence of nurses, with correlation coefficients ranging from r = –0.063 to r = 0.067 and all p-values >0.05. These findings suggest that patients evaluate nurses’ communicative competence independently of their socio-demographic profiles. Conclusion: The study concludes that nurses demonstrate satisfactory communicative competence, yet gaps in contextual awareness remain. The study provides preliminary evidence supporting the universality of patient expectations for empathetic, participatory, and culturally sensitive communication. Findings emphasize the need for targeted professional development and institutional strategies to enhance consistent, patient-centered communication in similar healthcare settings.